101 Engineering gamma/delta T cells with the T-Cell antigen coupler receptor effectively induces antigen-specific tumor cytotoxicity in vitro and in vivo. (10th December 2020) - Asbury, Sarah; Yoo, Seung Mi; Bramson, Jonathan
Abstract : Background: Engineered T cell therapies have revolutionized treatment of relapsed refractory haematological malignancies, however the cost of treatment for autologous products remains a significant challenge to their widespread use. The high cost is driven largely by the need for personalized manufacturing of autologous cell products. A non-conventional class of T cells, the gamma/delta T cell, can be safely transplanted into an unrelated recipient without inducing graft-versus host disease, 1 making them an ideal candidate for mass-manufactured off-the-shelf T cell therapies. We have previously described a novel method of directing conventional alpha/beta T cells towards tumour targets by co-opting the T cell receptor using the T cell Antigen Coupler (TAC) receptor. 2 Here, we describe the use of TAC receptors to engineer antigen-specific reactivity into gamma/delta T cells, resulting in highly potent anti-tumor cytotoxicity. Methods: Engineered gamma/delta T cells were manufactured by activating PBMCs with Zoledronate and IL-2. The TAC transgene was introduced into T cells using either VSV-G pseudotype lentivirus or GALV-psuedotyped gamma-retrovirus vectors.Through optimization studies, we determined transduction was highest 24 hours post-activation for lentivirus and 72 hours post-activation for gamma-retrovirus. Cultures were fed with IL-2 supplemented media every 2 – 3 days and enriched on Day 14 to >99% gamma/delta T cell purity using CD4/CD8 magnetic-activated cell sorting depletion (Miltenyi Biotec). Results: Both methods of gene transfer tested for our pilot study yielded excellent gene transduction (40% - 70%). Using lentivirus-engineered gamma/delta T cells, we demonstrated that the TAC receptor re-directs gamma/delta T cells to attack tumors in an antigen-specific manner. The presence of the TAC receptor did not interfere with lysis of tumor cells via the natural tumor-reactive gamma/delta T cell receptors. Importantly, TAC-engineered gamma/delta T cells displayed robust cytotoxicity at very low effector:target ratios (<1) and caused regression of human tumor xenografts that were otherwise resistant to non-engineered gamma/delta T cells. Curiously, gamma/delta T cell manufacturing was sensitive to the quality of the lentivirus product, where products with low titers were associated with outgrowth of conventional alpha/beta T cells. Outgrowth of alpha/beta T cells was not observed with gamma-retroviruses. We are presently evaluating the anti-tumor activity of gamma-retrovirus-engineered gamma/delta T cells. Conclusions: Off-the-shelf engineered gamma/delta T cells represent a strategy to reduce manufacturing cost and may represent the next generation of engineered T cell therapies.TAC receptors provide a robust tool for directing gamma/delta T cells to attack tumors that are otherwise resistant to gamma/delta T cells and should be evaluated further. Acknowledgements: This work was supported by the Samuel Family Foundation, the Ontario Centres of Excellence and Triumvira Immunologics. Ethics Approval: The study was approved by McMaster's Animal Research Ethics Board, AUP#19-02-10. References: Arruda LCM, Gaballa A, Uhlin M. Impact of γδ T cells on clinical outcome of hematopoietic stem cell transplantation: systematic review and meta-analysis. Blood Adv 2019;3(21):3436–3448. Helsen CW, Hammill JA, Lau VWC, et al. The chimeric TAC receptor co-opts the T cell receptor yielding robust anti-tumor activity without toxicity. Nat Commun 2018;9(1):3049.